Rod Bergenia - obsahové látky a biologická aktivita - Hendrychová, Helena; Tůmová, Lenka (Ceska a Slovenska farmacie, 2012)
Bergenia, a genus included in the family Saxifragaceae, is a valuable source of healing matters. About 30 Bergenia species are known all over the world. Scientific research is focused on five species mainly distributed in the mountains of Central and East Asia: Bergenia ciliata (Haw.) Sternb., Bergenia stracheyi Engl., Bergenia crassifolia (L.) Fritsch, Bergenia ligulata (Wall.) Engl. and Bergenia himalaica Boriss. These taxons belong to the widely used medicinal herbs in the traditional Chinese, Nepalese and Indian medicine, for therapy of cough and pulmonary diseases, to stop bleeding, to increase immunity and to dissolve kidney or bladder stones. Bergenia consists of many different active compounds including bergenin, norbergenin, catechin, gallic acid, arbutin and other polyphenols. In the Czech Republic this species is commonly grown but it is not used for medical therapy. Individual parts of this plant demonstrate an interesting biological activity, and antibacterial, antiviral, cytoprotective and antioxidant effects.
Keywords: Saxifragaceae; Plants, Medicinal; Plant Extracts; rostlinné extrakty; léčivé rostliny